THE CALCIUM SUPPLEMENTATION DURING PREGNANCY AGAINST DISORDERS OF GROWTH AND DEVELOPMENT OF TODDLERS - Layla Imroatu Zulaikha; Uliyatul Layli; Qurratul A’yun; Yulia Paramita Rusady (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Golden age is the initial stage of growth and development of toddlers starting covering the first 1000 days of life starting from the womb until toddlers are 2 years old which parents should not miss. This golden period can affect the quality of toddlers in the future, therefore the attention of parents must be maximally devoted to this period. Indonesia is a developing country with a national prevalence of under five nutritional status consisting of 3.9% poor nutrition, 13.8% malnutrition, 79.2% good nutrition and 3.1% excess nutrition. The growth of Indonesian toddlers under 5 years of age who experience deviations was reported by WHO in 2016 with a prevalence of 7,512.6 per 100,000 population (7.51%) (WHO, 2018). The results of the analysis obtained a correlation value of 0.547 indicating that there is an effect of calcium supplementation on the growth and development of toddlers. Good calcium supplementation during pregnancy which starts to be consumed in the 2nd trimester using prophylactic doses is very good for the growth of toddlers, especially those related to bones and teeth, as well as gross motor development.